Pemanfaatan zeolit sebagai bahan pengisi dalam pembuatan karet sponge untuk tatakan sepatu - Herminiwati Herminiwati; Murwati Murwati; Sri Brataningsih Puji Lestari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2007)
The purpose of this research was to study the effect of zeolite as filler in the preparation of sponge rubber for shoe insocks. During wearing period of shoes, unpleasant odor often smell for the result of sweat accumulation and their decomposition by microorganism. Besides as rubber filler, zeolit has odor adsorption function. The formula of rbber sponge could be as the following : crepe rubber 100 phr, paraffinic oil 20 phr, ZnO 10 phr, stearic acid 5 phr, MBTS 1 phr, TMTD 0.25 phr, anti-oxidant 1 phr and sulphur 2 phr. To obtain the best sponge rubber formula, some experiment was done by formulating variation of zeolite and blowing agent AZDM in the amount of 25, 50, 75 phr and 5, 10, 15 phr respectively. The vulcanization process was carried-out at temperature 140oC for minutes by compression moulding. The research showed that the best formula with high odor absorption was consist of zeolite 50 phr and blowing agent AZDM 5 phr. The sponge rubber had odor adsorption 93,47%, and the physical properties were as follow: tensile strength 2.018 N/mm2, elongation at break 251%, tear strength 1.029 N/mm2, density 0.717 g/cm3, and compression set 36.38%. Odor absorption was tested by using gas chromatography. Key words : zeolite,filler, sponge, rubber, shoe insocks. ABSTRAKPenelitian ini bertujuan untuk mempelajari pengaruh penggunana zeolit sebagai bahan pengisi dalam pembuatan karet sponge untuk tatakan sepatu. Pada pemakaian sepatu seringkali timbul bau tak sedap karena akumulasi keringat dan perurainnya oleh mikroorganisme. Zeolit selain sebagai bahan pengisi karet juga berfungsi sebagai peneyrap bau. Formula karet sponge terdiri atas karet krep 100 phr, minyak parafinik 20 phr, ZnO 10 phr, asam stearat 5 phr, MBTS 1 phr, TMTD 0,25 phr, anti oksidan 1 phr, belerang 2 phr. Untuk mendapatkan formula karet sponge terbaik maka peneltiian dilakukan dengan variasi bahan pengisi zeolit sebesar 25,50, 75 phr dan bahan pengembang AZDM sebesar 5, 10, 15 phr. Vulkanisasi dilakukan pada suhu 140 oC selama 10 menit dengan proses cetak tekan. Hasil penelitian menunjukkan bahwa formula terbaik dengan daya serap bau tinggi terdiri atas zeolit 50 phr dan bahan pengembang 5 phr. Karet sponge mempunyai daya serap bau 93,47% dan sifat fisis sebagai berikut: tegangan putus 2,018 N/mm2, perpanjangan putus 521%, ketahanan sobek 1,029 N/mm2, bobot jenis 0,717 g/cm3, pampat tetap 36,38%. Daya serap bau diuji menggunakan gas kromatografi. Kata kunci : zeolit, bahan pngisi, karet sponge, tatakan sepatu